Interactive Learning Application (Hijaiyah Letters) for Early Age Children - Hanik Hidayati; Rizkysari Meimaharani; Esti Wijayanti (SEAN Institute, 2023)
Interactive learning media is needed to encourage desire students in studying a science. In the learning process, children also learn about the science of reading the Koran. The use of technology is needed to create learning media that can support the learning process. One learning media that can support the learning and teaching process is an interactive learning application. The Hijaiyah Letter Interactive Learning Application is an Android-based learning application created with the aim of making it easier for children to learn how to read the Al-Qur'an via cellphone. This application aims to make it easier for children to learn the Koran and make the learning process more enjoyable pleasant.